Assessments of coastal erosion in rivers state, Nigeria, using global cover 30 - M. Menegbo , Emmanuel (International Journal of Physical Research, 2023)
Coastal dynamics and erosion are phenomena that have a considerable impact on inhabitants of coastal areas, regardless of whether the ac-tivity driving them is natural or manmade. Because a high percentage of the world's population lives along the shoreline, a raise in sea level will have a substantial effect on many people. Additionally, it will have an effect on low-lying coastal areas and islands. Using satellites for coastal management and monitoring changes in land cover and land use, it is possible to gain a better understanding of global changes in Coastal Erosion, especially in Rivers State, Nigeria. This study investigated coastal erosion in Rivers state, Nigeria, utilizing Global cover 30 land cover data. GIS and post-processing data were utilized to track changes occurring over the twenty-year period from 2000 to 2020. Two distinct temporal frames were identified within the given time span. The result of the analysis indicated that there was more erosion as the gain by the major Rivers indicated erosion along the coastline, Furthermore, changes of 47151000m2 were observed within 2000 and 2020, that is a period of twenty years with over 47151km2 land lost within Rivers state coastline. It is suggested that regular utilization of remote sensing data and geographic information system together with ground surveys be employed to monitor erosion rates, thereby assist-ing in pinpointing the most advantageous sites for protective barriers along the Nigerian coast in an effort to curtail coastal erosion.